Development of Interactive Multimedia Based on Adobe Flash as a Learning Media Steps of Geographical Research - Arifia Mawardani; M. Mirunalini; Chaloemphon Meechi; Smruti Shah (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: This study aims to develop interactive geography learning multimedia on appropriate and effective geography research step material. The product produced is in the form of interactive learning multimedia that can be used as a learning medium as well as a learning resource for students for material on geographic research steps. Methodology: This research is a development research (R & D) with a comparative descriptive analysis technique. sampling technique Simple Random Sampling. Data collection techniques were carried out through questionnaires and tests. The trials carried out consisted of small group trials and field trials. Main Findings: The results obtained show that: (1) The development which was carried out using the development model of Walter Dick and Lou Carrey was developed using a combination of simulation models and drills based on Adobe Flash; (2) Interactive multimedia based on Adobe Flash is proven to be appropriate for use as a learning medium for class X senior high school